Pengaruh Model Inquiry Training Berbantuan Media Assemblr Terhadap Kemampuan Literasi Sains Peserta Didik - Siska Rahayu; Muliani Muliani; Nurul Fadieny; Nanda Novita; Munzir Absa (Journal on Education, 2024)
Scientific literacy is scientific knowledge that is used to identify various questions and draw conclusions based on facts. Based on the interview results, students' scientific literacy abilities were not optimal, this research was conducted with the aim of finding out the effect of the inquiry training model assisted by Assembler media on students' scientific literacy abilities. This research is quantitative research using quasi-experimental research and a nonequivalent control group design. The sampling technique chosen was a total sampling of 48 students, namely 24 students in class XI-IPA 1 as the control class and 24 students in class XI-IPA 2 as the experimental class. The instruments used in this research used non-test instruments in the form of interviews and test instruments in the form of pretest and posttest questions in the form of essays totaling 10 questions. Meanwhile, data analysis uses prerequisite tests which include normality, homogeneity and hypothesis testing. The research results showed that the average scientific literacy pretest score for the experimental class, namely class XI-IPA 2, was 35.21 with a posttest score of 76.46, while the control class, namely class the results of the statistical hypothesis test obtained a Sig value. (2-tailed) of 0.000 with a significance level of 0.05. It can be concluded that there is an influence of the inquiry training model assisted by assembler media on students' scientific literacy abilities.